The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5455/medscience.2015.04.8255
|View full text |Cite
|
Sign up to set email alerts
|

Talar Osteochondral Defects

Abstract: Intra-articular ankle injuries to the talar body is one of the common cause of athletic disability that have been estimated to occur in approximately 6.5% of the ankle sprains and commonly affect the dome of the talus. Patients are commonly referred to the clinics with an acute injury to the ankle or with chronic ankle instability. This article describes the clinical presentation and imaging to diagnose of talar osteochondral defects. The treatment optionsare also reviewed to give consensus on optimal treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Indeed, at least from the owners' HCPI score side, the results could be attributed to a placebo effect. However, a number of randomized, controlled trials demonstrated variable efficacy of the major treatments (HA, PRP, or NSAIDS) in both dogs and humans [40][41][42][43][53][54][55][56][57][58][59][60][61]. Furthermore, we have additional unpublished data regarding the use of bone marrow-derived MSCS in dogs affected by spontaneous OA where, despite good clinical results, extended culture time, the need for specialized facilities, and high-costs make it more limited compared to MFAT.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, at least from the owners' HCPI score side, the results could be attributed to a placebo effect. However, a number of randomized, controlled trials demonstrated variable efficacy of the major treatments (HA, PRP, or NSAIDS) in both dogs and humans [40][41][42][43][53][54][55][56][57][58][59][60][61]. Furthermore, we have additional unpublished data regarding the use of bone marrow-derived MSCS in dogs affected by spontaneous OA where, despite good clinical results, extended culture time, the need for specialized facilities, and high-costs make it more limited compared to MFAT.…”
Section: Discussionmentioning
confidence: 99%
“…The chondral lesion is the most common musculoskeletal defect that usually affects old age individuals[43]. Damage affecting chondral and bony part of the joint is called osteochondral defect, when solely articular cartilage is affected the term chondral injury or defect is usually applied[44] [45]. Articular cartilage damage may found isolated, but associated tissues are always involved[46].…”
mentioning
confidence: 99%
“…Ligaments laceration is usually associated with traumatic injuries[52]. Etiology of the osteochondral lesions is also due to other causes rather than trauma such as metabolic defects, ischemia, joint degenerative disease, thromboembolism, corticosteroids or inflammatory diseases[45] [54].…”
mentioning
confidence: 99%